The Effect of Hydration on Urine Color Objectively Evaluated in CIE L*a*b* Color Space - Belasco, Rebekah; Edwards, Tory; Munoz, A. J.; Rayo, Vernon; Buono, Michael J. (Frontiers in Nutrition, 2020)
Urine color has been shown to be a viable marker of hydration status in healthy adults. Traditionally, urine color has been measured using a subjective color scale. In recent years, tristimulus colorimetry developed by the International Commission on Illumination (CIE L*a*b*) has been widely adopted as the reference method for color analysis. In the L*a*b* color space, L* indicates lightness ranging from 100 (white) to 0 (black) while a* and b* indicate chromaticity. a* and b* are color directions: -a* is the green axis, +a* is the red axis, -b* is the blue axis, and +b* is the yellow axis. The L*a*b* color space model is only accurately represented in three-dimensional space. Considering the above, the purpose of the current study was to evaluate urine color during different hydration states, with the results expressed in CIE L*a*b* color space. The study included 28 health participants (22 males and 6 females) ranging between the age of 20 and 67 years (28.6 + 11.3 years). One hundred and fifty-one urine samples were collected from the subjects in various stages of hydration, including morning samples after 7-15 hours of water deprivation. Osmolality and CIE L*a*b* parameters were measured in each sample. As the urine osmolality increased, a significant linear increase in b* values was observed as the samples became more pronouncedly yellow (τb = 0.708). An increase in dehydration resulted in darker and significantly more yellow urine, as L* values decreased in lightness and b* values increased along the blue-yellow axis. However, as dehydration increased, a notable polynomial trend in color along the green-red axis was observed as a* values initially decreased, indicating a green hue in slightly dehydrated urine, and then increased as urine became more concentrated and thus more dehydrated. It was determined that 74% of the variance seen in urine osmolality was due to CIE L*a*b* variables. This newfound knowledge about urine color change along with the presented regression model for predicting urine osmolality provides a more detailed and objective perspective on the effect of hydration on urine color, which to our knowledge has not been previously researched.